If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z*7+9=2
We move all terms to the left:
z*7+9-(2)=0
We add all the numbers together, and all the variables
z*7+7=0
Wy multiply elements
7z+7=0
We move all terms containing z to the left, all other terms to the right
7z=-7
z=-7/7
z=-1
| 3x^2-9x-+1=0 | | 7/8=v-5/6 | | 112+5x=7(3-4x)+20x | | 4v+12=80 | | P(x)=5x^2+6x+1 | | 12z+2z+4z-9z-5z=4 | | 180-(3x+2)-(2x-12)=0 | | 7x-42=3x+48 | | 3x+(7x–21)+(4x–9)=180 | | z-1/5=3 | | 10x-(21-4x)=11(5-2x) | | 2y+14=6y-2 | | 4u+15=43 | | -3+28x=5(3+2x) | | 48x^2+0x+39=0 | | 5(2x-1)=7x-29 | | .(5x–23)+(7x–13)=180 | | 3x/9=10 | | 104=-2x | | 8y-2y=6 | | 12m-15m=12 | | -2(x+15)=3x | | -14x+7+11x=-3-3x | | -3x=5(x-24) | | 2(n-7)=31 | | -8x+4x=100 | | 2x=9(28+x) | | 1x+160+4=20 | | 4x+2=3×-12 | | 17-5,8x=17 | | x+28=−8 | | 5a+6a+15-40=180 |